The Anterior Transverse Ligament of Knee: Morphological and Morphometric Study in Formalin Fixed Human Fetuses. - Murlimanju BV,; Narga N,; Ashwin K,; Mangala MP,; Naveen K,; Chandni G,; Biswabina R,; Chettiar GK, (Department of Surgery, UKM Medical Centre, 2014)
The objective was to study the morphology and morphometry of transverse ligament of the knee joint in south Indian population. The present study included 53 formalin fixed foetuses which were obtained from the department of Anatomy. There were 106 knee joints which were available for the present study. A vernier caliper of 0.02 mm accuracy was used to measure the length of the transverse ligament. Among our specimens, transverse ligament of the knee was observed in 87.7% of the cases. It was observed bilaterally in 81.1% of cases. The double transverse ligaments were not observed in any of our specimens. The mean length of the transverse ligament measured 3.7 ± 1.5 mm. The statistically significant difference was not observed between the right and left sided transverse ligaments or gender with regard to its length (Student's t test; p > 0.05). The morphological and morphometric data related to the transverse ligament of the knee in human foetuses have not been reported. The present study provides additional information on the morphology and morphometry of the transverse ligament in human foetuses. We believe that the data of the present study will provide support to the foetal anatomy, concerning the surgical procedures and arthroscopy of the knee joint. The findings are enlightening not only for Orthopedic Surgeons, but also for the Morphologists and Embryologists.